Saúde escolar: descrição e análise de um Programa de Fonoaudiologia em Rede Escolar pública de Ensino Fundamental I - Souza, Elaine Aguiar de (2023)
Introduction: The school environment is a facilitating scenario for the prevention of injuries and for health promotion, which corroborates the intersectoral work of Health with Education. In this contexto, the Exchange of knowledge and practices between the speech therapist and the educator can generate reciprocal gains: for speech therapists, a greater knowledge of the school reality and na improvement of their health practices aimed at the school population; to the teachers, specific knowledge in the área of health about development, the learning process anda Other issues worked on by Speech Therapy. Objective: to presente and evaluate the Speech Therapy Guidance Program to teachers in the city of Embu-Guaçu, within the scope of the Health at School Program – PSE. Method: descriptive, retrospective research with case study design. The study was carried out with 52 teachers, using three strategies: a questionnaire and na interview before and after going through the Program and a Discussion Group (DG) after the Program was Applied with teachers who were willing to participate in the activity. Results: both in the questionnaires and in the interviews, there was a change in the teachers perception regarding the contributions of the speech therapist. In the Discussion Group (GD), the research subjects were unanimous in affirming the relevance of the Program, pointing to the need for systematic and permanente intersectoral work, as well as suggesting that the speech therapist better understand the reality of teachers and schools. Conclusion: there was greater interaction between teachers and speech therapists during the Program, as proposed by the PSE. However, this interaction is still in its infancy, it needs to advance so that, in fact, such a professional relationship becomes regular and systematic, allowing a more adequate management of school demands related to learning difficulties, which would also require the opening of this relationship (Education/ speech therapy) to other professions and áreas of knowledge